Effects of bromelain and lyophilized pineapple juice on orthodontically induced root resorption in male guinea pigs a scanning electron microscopy study - Veleña, Harvenio Omar E., VI
General Objective: The aim of this investigation is to determine the effect of lyophilized pineapple juice and commercially available bromelain preparation on the root surface of guinea pigs during orthodontic tooth movement utilizing scanning electron microscopy.